DEVELOPMENT OF ALPHA POWER EXPONENTIATED TOPP-LEON INVERSE WEIBULL DISTRIBUTION - Mohammed, Yusuf Ibrahim; Bakari, H. R.; Mohammed, Y. A. (FUDMA Journal of Sciences, 2026)
Lifetime data in engineering, medical, and reliability studies often exhibit complex hazard rate and tail behaviors that classical distributions, such as the inverse Weibull model, cannot adequately capture. To address this limitation, this study proposes a new and flexible lifetime model called the Alpha-Power Exponentiated Topp-Leone Inverse Weibull (AP-ETLIW) distribution. The proposed model is constructed by integrating the exponentiation mechanism, the Topp-Leone transformation, and the alpha-power transformation into the inverse Weibull distribution, thus enhancing shape flexibility, hazard rate variation, and tail behavior. The performance of the AP-ETLIW distribution is evaluated through comparisons with existing lifetime models, demonstrating its superior fitting capability in various applications, including reliability analysis, survival analysis, engineering and medical sciences. This study contributes to the development of hybrid statistical distributions and provides a robust tool to model complex lifetime data.
Keywords: Alpha Power; Topp Leon; Exponentiated; Weibull Distribution; Properties; Application